2017
DOI: 10.1155/2017/2069519
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive Removal of Benzene and Toluene from Aqueous Environments by Cupric Oxide Nanoparticles: Kinetics and Isotherm Studies

Abstract: Removal of benzene and toluene, as the major pollutants of water resources, has attracted researchers' attention, given the risk they pose to human health. In the present study, the potential of copper oxide nanoparticles (CuO-NPs) in eliminating benzene and toluene from a mixed aqueous solution was evaluated. For this, we performed batch experiments to investigate the effect of solution pH (3-13), dose of CuO-NPs (0.1-0.8 g), contact time (5-120 min), and concentration of benzene and toluene (10-200 mg/l) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The results revealed that PP can degrade soil TPH and significantly enhance the biodegradation rate in unsaturated diesel-contaminated soil when combined with bioaugmentation foam. Advanced oxidation processes (ozone, ozone, hydrogen peroxide, ozone/ultraviolet, hydrogen peroxide/ultraviolet) are suitable alternatives for decomposing organic biodegradable organic waste from conventional wastewater treatment [103,104]. The advanced oxidation process has significant advantages (such as the lack of high levels of sludge production) compared to conventional filtration methods.…”
Section: Advanced and Chemical Oxidationmentioning
confidence: 99%
“…The results revealed that PP can degrade soil TPH and significantly enhance the biodegradation rate in unsaturated diesel-contaminated soil when combined with bioaugmentation foam. Advanced oxidation processes (ozone, ozone, hydrogen peroxide, ozone/ultraviolet, hydrogen peroxide/ultraviolet) are suitable alternatives for decomposing organic biodegradable organic waste from conventional wastewater treatment [103,104]. The advanced oxidation process has significant advantages (such as the lack of high levels of sludge production) compared to conventional filtration methods.…”
Section: Advanced and Chemical Oxidationmentioning
confidence: 99%
“…A number adsorbents have been developed and studied for the removal of benzene from gas flow, including aerogel silica/Merck activated carbon [11], carbonized polydopamine adsorbent [29], unimodal and bimodal silica-based mixedmetal oxides [30], Cupric Oxide Nanoparticles [31], and activated rice ash [32], and benzene adsorption capacities in the range of a few mg/g to about 1 g/g has been reported for them.…”
Section: Removal Of Benzene By CX and Acxmentioning
confidence: 99%
“…Due to the unique properties of NPs, the adsorption processe was obtained with high efficiency and recovery [16]. The cupric oxide nanoparticles (CuONPs) have been used for adsorptive removal of benzene and toluene from aqueous environments [17]. Due to previous studies, the different methods such as, adsorption [18,19], the photo-catalytic oxidation and thermal oxidation [20] were used for removal of VOC's or BTEX in environment matrixes.…”
Section: Introductionmentioning
confidence: 99%